Psikiyatrik Semptomlarla Başvuran Nörowilson Olgusunda Reversibl Kranial MRG Bulguları - Koç, Mustafa; Serhatlıoğlu, Selami; Orhan, Hacı (Fırat University, 2007)
Wilson hastalığı; otozomal resessif geçiş gösteren, bakır metabolizmasındaki bozukluktan kaynaklanan metabolik bir depo hastalığıdır. Hastalığın semptomları; karaciğer, beyin, kornea, böbrek ve diğer dokularda toksik bakır birikimi ile gelişir. Wilson hastalığı tanısı, 5-40 yaş arasında nörolojik ve psikiyatrik semptomlar sergileyen hastalarda göz önünde bulundurulmalıdır. MRG de izlenen en sık anormallik, T2 ağırlıklı görüntülerde lentiküler, talamik ve kaudat nükleusta ayrıca beyaz cevherde artmış sinyal intensiteleridir. Tedavi sonrasında bazal ganglionlardaki sinyal intensiteleri kaybolabilmektedir. Hastalığın tanı, tedavi ve radyolojik görüntüleme özelliklerinin bilinmesi önemlidir. Çünkü erken tanı ve tedavi ile hastalardaki onarılamayan doku hasarı önlenebilmekte, buna bağlı olarak prognoz olumlu yönde etkilenmektedir. Biz bu olgumuzda kranial MRG de Wilson hastalığının tutulumu ile uyumlu sinyal değişiklikleri tesbit edilen hastanın, tanı anında ve tedavi sonrasında oluşan MRG görüntü özelliklerini tartıştık. ©2007, Fırat Üniversitesi, Tıp Fakültesi

Wilson's disease is a metabolic storage disease resulting from the malfunction in the copper metabolism showing autosomal recessive progress. The symptoms of the disease become apparent with the buildup of toxic copper residues in the liver, brain, cornea, kidney and other tissues. The diagnosis of the Wilson's disease should be taken into account in the patients showing neurological and physiological symptoms between the ages of 5 and 40. The most widely viewed abnormalities in T2 dominant images of MRI are the increased intensities in lenticular, thalamic, nucleus caudatus and the white matter. The signal intensities may disappear in the basal ganglia after the treatment. It is important to know the pre-diagnosis, treatment and radiological screenings of the disease. Because, if the disorder is detected early and treated correctly, the irreversible tissue damage can partly be prevented, thus the prognosis is positively affected. We report a case where cranial MRI shows signal intensities of Wilson disease, to discuss the characterization of MRI imaging at diagnosis and after treatment. ©2007, Firat University, Medical Faculty
Reversible Cranial MRI Findings of Neurowilson Case Hospitalized with Phsiciatric Sympthomps